2004
DOI: 10.1183/09031936.04.00106803
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of99mTc‐DTPA and urea for measuring cefepime concentrations in epithelial lining fluid

Abstract: The efficacy of antimicrobial agents against pulmonary infections depends on their local concentrations in the lung. The aims of the present study were to: 1) compare technetium-99m diethylenetriaminepenta-acetic acid ( 99m Tc-DTPA) and urea as markers of epithelial lining fluid (ELF) dilution for measuring ELF concentrations of pharmaceuticals; 2) quantify ELF cefepime concentrations in normal and injured lung; and 3) measure the increase in permeability to cefepime following oleic acid-induced acute lung inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The ELF exposures (based on the AUC 0 -8 ) for cefepime and zidebactam were approximately 35% to 39% of the total plasma concentrations. The penetration ratios for cefepime are similar to those reported in animal studies and are lower than those observed with continuous infusions in critically ill patients (18,19). The ratios of ELF to total plasma concentrations of cefepime and zidebactam gradually increased (e.g., from approximately 0.31 to 0.95) throughout the 10-hour BAL sampling times after the seventh dose (Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 81%
“…The ELF exposures (based on the AUC 0 -8 ) for cefepime and zidebactam were approximately 35% to 39% of the total plasma concentrations. The penetration ratios for cefepime are similar to those reported in animal studies and are lower than those observed with continuous infusions in critically ill patients (18,19). The ratios of ELF to total plasma concentrations of cefepime and zidebactam gradually increased (e.g., from approximately 0.31 to 0.95) throughout the 10-hour BAL sampling times after the seventh dose (Tables 3 and 4).…”
Section: Discussionsupporting
confidence: 81%
“…The use of BAL fluid to determine ELF drug concentrations is a commonly used approach; however, large differences in antibiotic ELF concentrations using this method have been observed (32,33). Using results from healthy subjects may also underestimate antibiotic concentrations at the site of infection, because penetration of antibiotics into the lung of pneumonia patients may be higher as a result of the increased permeability of inflamed lung tissue (32,34). The methodology used to evaluate antibiotic concentrations in the lung continues to develop and serves as a valuable tool in evaluating antibiotics for the treatment of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…BALF was collected in order to assess TMC353121 concentrations in the lung epithelial lining fluid (ELF) after correction for the dilution with lavage fluid. A single lavage with a short dwelling time was applied as previously recommended for better accuracy of the determination of ELF dilution (2). BSA was added to the lavage fluid in order to prevent the adsorption of TMC353121 to syringes or other containers.…”
Section: Methodsmentioning
confidence: 99%